Short report on the excavations in the legionary fortress of Brigetio (2017–2018) - Bartus, Dávid; Borhy, László; Joháczi, Szilvia; Számadó, Emese (Dissertationes Archaeologicae, 2019)
After the aerial archaeological surveys of the preceding years, a new excavation project has been started in 2017 in the northern part of the legionary fortress of Brigetio. The main result of the seasons of 2017 and 2018 were the unearthing of a large Late Roman apsidal building, which can be most probably connected to the death of Valentinian I.